Design of A 11 KWp Grid Connected Solar Photovoltaic Power Plant on 100 m2 available Area in the Birbhum District of West Bengal - Ganguli, Souvik; Sinha, Sunanda (Journal of the Institute of Engineering, 2011)
The depletion of fossil fuel resources on a worldwide basis has necessitated an urgent search for alternative energy sources to meet present day demands. Solar energy is a clean, inexhaustible and environment-friendly potential renewable energy option. A stand-alone solar photovoltaic cannot provide a continuous supply of energy due to seasonal and periodic variations. Therefore, in order to satisfy load demand, grid connected energy systems are now being implemented that combine solar and conventional conversion units. The objective of this work is to estimate the potential of grid quality solar photovoltaic power in the Birbhum district of West Bengal and develop a system based on the potential energy estimated for an available land area of 100 m2. Specific equipment specifications are utilized based on the availability of components in India. Key Words: Diurnal variations; Daily Energy Output; Monthly Energy Output; Grid Connected Photovoltaic (PV) System; PWM Inverters; Solar Radiation; Yearly Energy Output DOI: http://dx.doi.org/10.3126/jie.v8i1-2.5100 Journal of the Institute of Engineering Vol. 8, No. 1&2, 2010/2011 Page: 105-112 Uploaded Date: 20 July, 2011